Perancangan Augmented Reality (AR) Sebagai Media Promosi Objek Wisata Berbasis Android - Arsy Febrina Dewi; M. Ikbal (Infotek: Jurnal Informatika dan Teknologi, 2022)
Tourism is one of the most important things for an area. Interesting and crowded tourism shows the progress of the area. One way to promote tourism is by media promotion. There are many ways that can be used for promotion, one of which is by utilizing information technology based on Augmented Reality (AR). AR is a technology that displays 3D virtual objects into a real environment and builds visualization of 3D images in tourist brochures to be more informative. AR helps users get clearer information about the attractions they want to visit in Langsa city. The use of AR on Android makes the system more accessible to users. Based on trials, the AR system was successfully implemented on the Android system. In addition, camera trials were also carried out based on distance, tilt angle, and lighting when detecting tourist attraction markers. The result is that the camera successfully detects the target image (marker) and generates a 3D animation of a tourist attraction. However, the best results in detecting markers are distances above 15cm at an angle with cloudy sunlight lighting criteria.